2014
DOI: 10.1177/0027432114544376
|View full text |Cite
|
Sign up to set email alerts
|

How Critical Is Critical Thinking?

Abstract: Recent educational discourse is full of references to the value of critical thinking as a 21st-century skill. In music education, critical thinking has been discussed in relation to problem solving and music listening, and some researchers suggest that training in critical thinking can improve students' responses to music. But what exactly is meant by "critical thinking"? This article explores how critical thinking, when thought of as an outgrowth of Critical Theory and pedagogy concepts, may look very differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 3 publications
1
23
0
8
Order By: Relevance
“…Bloch and Spataro (2014) suggest that cultivating a culture of critical-thinking is a necessary approach to implementing critical thinking in the classroom. From a pedagogy viewpoint, critical thinking is viewed as a method that encourages students to take an active role in questioning and challenging the norms, which may lead to critical action toward changing the status quo (Shaw, 2014). A meta-analysis conducted by Huber and Kuncel (2016) showed that critical thinking significantly improved over the course of a normal college experience, although including critical thinking as part of the curricula did not necessarily generate incremental long-term gains.…”
Section: Critical Thinkingmentioning
confidence: 99%
“…Bloch and Spataro (2014) suggest that cultivating a culture of critical-thinking is a necessary approach to implementing critical thinking in the classroom. From a pedagogy viewpoint, critical thinking is viewed as a method that encourages students to take an active role in questioning and challenging the norms, which may lead to critical action toward changing the status quo (Shaw, 2014). A meta-analysis conducted by Huber and Kuncel (2016) showed that critical thinking significantly improved over the course of a normal college experience, although including critical thinking as part of the curricula did not necessarily generate incremental long-term gains.…”
Section: Critical Thinkingmentioning
confidence: 99%
“…Keterampilan abad 21 diperlukan agar siswa dapat memecahkan masalah yang lebih kompleks, berkolaborasi dan berkomunikasi dengan baik, memiliki keterampilan untuk memperoleh informasi secara mandiri, dan mampu beradaptasi serta bersaing dalam perekonomian yang bersifat global saat ini (Gewertz, 2008). Dengan demikian lembaga-lembaga pendidikan di seluruh dunia harus dapat memperkenalkan keterampilan abad ke-21 kepada siswa melalui pendidikan formal (Colardyn & Bjornavold, 2004 (Shaw, 2014). Dengan demikian tidak semua pertanyaan guru dan tanggapan siswa bersifat permanen.…”
Section: A Pendahuluanunclassified
“…Studies of the development of teachers' critical thinking related beliefs are needed, with the goal of establishing teacher-education practices emphasizing appropriate use of high critical thinking activities for low-advantage learners [32]. [23]Critical thinking is active rather than passive and is of a higherorder and abstract nature.…”
Section: Professional Competencementioning
confidence: 99%